2023
DOI: 10.3389/fcimb.2023.1134433
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence-based innovative approaches to control catheter-associated urinary tract infection: a review

Abstract: Healthcare settings have dramatically advanced the latest medical devices, such as urinary catheters (UC) for infection, prevention, and control (IPC). The continuous or intermittent flow of a warm and conducive (urine) medium in the medical device, the urinary catheter, promotes the formation of biofilms and encrustations, thereby leading to the incidence of CAUTI. Additionally, the absence of an innate immune host response in and around the lumen of the catheter reduces microbial phagocytosis and drug action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 160 publications
(237 reference statements)
0
4
0
Order By: Relevance
“…Previous literature reports suggested that flagellated bacteria like E. coli can migrate from an infected catheter toward the bladder and reach the kidney via swarming, whereas in the case of S. aureus, it migrates via sliding, which is one form of motility .…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature reports suggested that flagellated bacteria like E. coli can migrate from an infected catheter toward the bladder and reach the kidney via swarming, whereas in the case of S. aureus, it migrates via sliding, which is one form of motility .…”
Section: Resultsmentioning
confidence: 99%
“…These environments may not only be non-uniform, but may also involve the combined effects of multiple magnetic fields. More importantly, in actual surgical applications, it is necessary to consider problems faced by interdisciplinary, such as biofilms [ 189 ] and infections related to catheters [ 190 , 191 ]. Although the literature [ 192 ] proposes a strategy for preventing biological infections, it still confronts multiple challenges [ 193 ].…”
Section: Magnetic Soft Robotsmentioning
confidence: 99%
“…In contrast to an acute wound, which is typically unrelated to biofilm, a chronic wound caused by biofilm endures and heals slowly. Although P. aeruginosa biofilms are embedded in the deep layers of wounds, biofilms typically grow on the outer layer of wounds and are challenging to diagnose using a standard wound swab culture [53,54].…”
Section: Clinical Implication Of Biofilmsmentioning
confidence: 99%